Analysis of Early Detection Implementation in Communicable Disease Program at Elderly Posyandu in Wet Rice, Langkat Regency - Dalimunthe, Ulfa Fadilla; Susilawati, Susilawati; Susanti, Nofi (Journal La Medihealtico, 2024)
Purpose: this study was to analyze the implementation of early detection in non-communicable disease programs at the elderly posyandu at the Beras Basah Health Center, Langkat District, North Sumatra.Methode: uses qualitative with a descriptive approach. Data collection techniques are carried out by observation, in-depth interviews and documentation. This study used SWOT analysis. Results: The implementation of early detection activities has not been optimal, which can be seen from inconsistencies in program implementation in the field. Limited medical equipment is also a significant obstacle, reducing the ability of officers to carry out effective early detection. Lack of village government participation and minimal awareness and family support for early detection activities also hamper the implementation of this program. Apart from that, the inadequate knowledge of posyandu cadres is a challenge in optimizing program implementation. Opportunity analysis shows that there are several strategic steps that can be taken to increase the effectiveness of this program. Advocacy and education to the village government regarding the benefits of posyandu for the elderly can increase support and participation from the local government. Providing support and assistance to elderly families will increase their awareness and participation in early detection activities. Training for posyandu cadres is also an important opportunity to increase their knowledge and skills in implementing early detection programs. Conclussion: The program for non-communicable diseases in the elderly is still underdeveloped and has not achieved its goal of ensuring the health of the elderly.